Some aspects of the chemistry of zirconium compounds relating to their combination with collagen - Williams-Wynn, David Ernest Arthur (Rhodes University, Faculty of Science, Department of Chemistry, 1960)
[Summary] Some properties of zirconium compounds in aqueous solution have been determined using physico-chemical techniques. Zirconium oxychloride was used as the source of zirconium in all detailed investigations; zirconium sulphate was used in a few cases for comparative purposes. The Stokes diaphragm cell method has been used to determine the diffusion coefficient of zirconium in hydrochloric acid solution. It was found that the diffusion coefficient fell progressively with time, a limiting value being reached 4 to 5 weeks after dissolving the salt, and it was demonstrated that particles in the aged solutions were more homogeneous than in freshly prepared solutions. The limiting values were concentration dependent; dilute solutions had a lower diffusion coefficient than the more concentrated solutions when measured at the natural pH. In the presence of added acid the rate of diffusion was increased until a limiting value was reached in 0.5 M acid. The addition of alkali or complexing acids reduced the rate of diffusion.
Keywords: Zirconium compounds; Collagen